Repairing gut barrier by traditional Chinese medicine: roles of gut microbiota - Zhou, Yaochuan; Zhang, Dandan; Cheng, Hao; Wu, Jinlu; Liu, Juan; Feng, Wuwen; Peng, Cheng (Frontiers in Cellular and Infection Microbiology, 2024)
Gut barrier is not only part of the digestive organ but also an important immunological organ for the hosts. The disruption of gut barrier can lead to various diseases such as obesity and colitis. In recent years, traditional Chinese medicine (TCM) has gained much attention for its rich clinical experiences enriched in thousands of years. After orally taken, TCM can interplays with gut microbiota. On one hand, TCM can modulate the composition and function of gut microbiota. On the other hand, gut microbiota can transform TCM compounds. The gut microbiota metabolites produced during the actions of these interplays exert noticeable pharmacological effects on the host especially gut barrier.Recently, a large number of studies have investigated the repairing and fortifying effects of TCM on gut barriers from the perspective of gut microbiota and its metabolites. However, no review has summarized the mechanism behand this beneficiary effects of TCM. In this review, we first briefly introduce the unique structure and specific function of gut barrier. Then, we summarize the interactions and relationship amidst gut microbiota, gut microbiota metabolites and TCM. Further, we summarize the regulative effects and mechanisms of TCM on gut barrier including physical barrier, chemical barrier, immunological barrier, and microbial barrier. At last, we discuss the effects of TCM on diseases that are associated gut barrier destruction such as ulcerative colitis and type 2 diabetes. Our review can provide insights into TCM, gut barrier and gut microbiota.